ArtScience Museum, Marina Bay Sands, Singapore - Basile Morin (Wikimedia Commons, 2018)
Notice iconographique issue de Wikimedia Commons. Titre: ArtScience Museum, Marina Bay Sands, Singapore. ArtScience Museum, Marina Bay Sands, in the late afternoon, in front of the skyline of the Central Business District, Singapore. Architect: Moshe Safdie.
Licence Creative Commons Attribution-Share Alike 4.0 via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons